Expert consensus on radiotherapy for oligometastatic esophageal cancer (2025 edition) (Radiation Medicine and Protection, 2025)
Approximately 40% of esophageal cancer patients have metastatic disease at the time of initial diagnosis. Although immunotherapy has changed the treatment pattern of advanced, recurrent, or metastatic esophageal cancer, the options for systemic treatment for these patients are still limited, and the prognosis is poor. Oligometastasis is an intermediate stage between locoregional and widespread systemic metastasis. Some studies have shown that combining systemic treatment with local treatment, such as radiotherapy, may improve the survival of patients with oligometastasis in various solid tumors, including esophageal cancer. At present, there is still a lack of data support from large randomized clinical trials on the timing, dose, and technique of radiotherapy for oligometastatic esophageal cancer. Based on recent studies on oligometastatic esophageal cancer, this consensus was jointly developed after in-depth discussions and multiple revisions by experts from the following organizations: Radiation Oncology Treatment Physician Branch, Chinese Medical Doctor Association; Branch of Radiation Oncology Therapy, Chinese Medical Association; Professional Committee of Radiotherapy for Cancer, Chinese Anti-cancer Association; Expert Committee of Esophageal Cancer, Chinese Cancer Radiotherapy Alliance. This consensus provides a relatively clear definition and classification of oligometastatic esophageal cancer. It summarizes common problems in radiotherapy based on current medical evidence to provide reference and academic guidance for the clinical practice of radiotherapy for oligometastatic esophageal cancer.